2016
DOI: 10.1111/ane.12717
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid cytotoxicity does not affect survival in amyotrophic lateral sclerosis

Abstract: Cerebrospinal fluid cytotoxicity was not associated with differential survival rates. This suggests that the presence of cytotoxicity in CSF, measured through neuronal viability in primary cultures of motor cortex neurons, could reflect different mechanisms of the disease, but it does not predict disease outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…Two studies also assessed cytotoxicity within ALS patient populations. In the first study, which evaluated CSF cytotoxicity in 31 patients with ‘probable’ or ‘definite’ ALS at the time of diagnosis, 67.7% of patients were considered to possess cytotoxic CSF, with cytotoxicity being defined as a reduction in cell survival greater or equal to 25% compared to control ( Galán et al , 2017 ). The second study compared CSF cytotoxicity between sporadic ALS patients with a high concentration of 4‐hydroxynonenal with those with a low concentration of 4‐hydroxynonenal, and reported a significant difference at both 1% and 10% CSF concentration ( Smith et al , 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies also assessed cytotoxicity within ALS patient populations. In the first study, which evaluated CSF cytotoxicity in 31 patients with ‘probable’ or ‘definite’ ALS at the time of diagnosis, 67.7% of patients were considered to possess cytotoxic CSF, with cytotoxicity being defined as a reduction in cell survival greater or equal to 25% compared to control ( Galán et al , 2017 ). The second study compared CSF cytotoxicity between sporadic ALS patients with a high concentration of 4‐hydroxynonenal with those with a low concentration of 4‐hydroxynonenal, and reported a significant difference at both 1% and 10% CSF concentration ( Smith et al , 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…We could not observe a significant reduction of MNs or neurons in general by exposition to ALS-CSF compared to control-CSF, when healthy donor-derived MNs were treated. Several reasons could explain this difference from results from murine primary cortical/spinal motor neuron cultures [3,47], including human vs. murine cell culture system, medium composition or preanalytic CSF preparation. Another major concern regards the cellular age.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was necessary due to the long time culture conditions and the protocol for human iPSC-derived MNs with the need for medium change every other day (Figure 1). Thus, we cannot answer the question as to whether single ALS patient-derived CSF might vary depending on clinical parameters such as ALS subtype, disease stage or even family background [47]. However, the study rationale was to investigate whether CSF from sporadic ALS patients could induce an MN-like degeneration in the dish, and thus we intended to analyze group differences rather than ALS subtype or individual patient's specific differences.…”
Section: Discussionmentioning
confidence: 99%
“…We have read the article written by Galán et al, 1 First, the association between independent variables with survival rate was assessed using the Cox PH models, while PH assumption as one of the major assumptions has not been evaluated graphically or using the appropriate methods such as time-dependent covariates methods. This assumption has been violated in the study conducted by Galán and colleagues which is shown in their article as Figure 1.…”
Section: Cerebrospinal Fluid Cytotoxicity Does Not Affect Survival Inmentioning
confidence: 99%